(untitled) (Research, Society and Development, 2025)
The search for biomaterials capable of stimulating periodontal tissue regeneration is ongoing. The literature extensively describes the use of different biomaterials and surgical techniques, such as bone grafts, guided tissue regeneration, and growth factors. With the discovery of enamel matrix–derived proteins in 1997, a new perspective emerged for periodontal regenerative therapies. Since then, enamel matrix derivative (EMD) has gained prominence due to its ability to modulate regenerative processes. EMD has been evaluated in different periodontal therapeutic approaches, including supraosseous and infraosseous defects, interradicular lesions (furcation defects), and gingival recessions, as well as in association with various biomaterials. The aim of this study was to elucidate, through an updated literature review, the clinical outcomes of different applications of EMD and its regenerative potential in contemporary periodontal therapy. The analyzed studies indicate that defect anatomy directly influences clinical outcomes, with greater improvements observed in deeper infraosseous defects. In the treatment of these defects, especially vertical defects and mandibular furcation lesions, EMD shows significant results when associated with basic periodontal therapy, although it does not demonstrate superiority compared with membrane-based approaches. In the treatment of gingival recessions, EMD demonstrates benefits in clinical parameters and contributes to the revascularization process. Regarding its association with other biomaterials, literature indicates advantages mainly when combined with bovine bone grafts. In contrast, its association with autogenous bone, bioglasses, and platelet-rich fibrin does not show significant additional benefits. Thus, the results reinforce the clinical applicability of EMD.